The implementation of a multi‐level reflective consultation model in a statewide infant & early childcare education professional development system: Evaluation of a pilot. Issue 2 (16th February 2022) - Shea, Sarah E.; Sipotz, Kelly; McCormick, Ashley; Paradis, Nichole; Fox, Brandy
Abstract: The growth in professional development for the infant‐early childhood workforce has necessitated the implementation of novel, sustainable approaches to meet infant early childhood mental health (IECMH) training and reflective supervision consultation (RSC) needs. The 12‐month pilot of a US statewide reflective consultation (RC) group model included IECMH consultants, grant specialists, supervisors, and program managers ( n  = 38) and their group reflective consultants ( n  = 6). The pilot evaluation provided an opportunity to design a study that assessed the impact of RC on infant‐early childhood professionals. The mixed‐methods study included an assessment of consultees' reflective practice skills and experience of their work. Findings included consultees' self‐reported increased reflective practice self‐efficacy and increased use of reflective practice skills. While there were no changes in the Maslach Burnout Inventory (MBI) personal accomplishment, emotional exhaustion, or depersonalization results, qualitative findings indicated a decrease in burnout and an increase in relationship‐based practice across professional roles. This unique pilot provides an example of an organizational approach to instituting RC with a broad spectrum of infant‐early childhood professionals and yields valuable information about the impacts of RC models on such professionals' work experience and professional practice. Resumen: El crecimiento en cuanto al desarrollo profesional para los trabajadores del área de infancia y temprana niñez ha necesitado de la implementación de acercamientos novedosos y sostenibles para cumplir con las necesidades de entrenamiento y consulta de supervisión con reflexión (RSC) del campo de la salud mental en la infancia y temprana niñez (IECMH). El plan piloto de 12 meses de un modelo de grupo de consulta con reflexión (RC) a lo largo y ancho de los estados de Estados Unidos incluyó consultores de IECMH, especialistas en fondos de financiación, supervisores y directores de programas (n = 38) y los consultores d reflexión de sus grupos (n = 6). L evaluación del plan piloto proveyó una oportunidad para diseñar un estudio que evaluara los impactos que RC tiene en los profesionales de infancia y temprana niñez. El estudio de métodos combinados incluyó una evaluación de las habilidades prácticas y experiencias reflexivas de trabajo de los consultantes. Los resultados incluyen los auto reportes de los consultantes sobre el aumento de la práctica reflexiva de auto eficacia y el aumento del uso de las habilidades de la práctica con reflexión. Aunque no se dieron cambios en cuanto a los logros personales, el agotamiento emocional o los resultados de despersonalización en el Inventario de Agotamiento de Maslach (MBI), los resultados cualitativos indicaron una baja en el agotamiento y un aumento en la práctica basada en la relación a lo largo de los roles profesionales. Este plan piloto único ofrece un ejemplo de un acercamiento organizacional para instituir RC con un enfoque amplio de los profesionales de la infancia y temprana niñez y aporta información de valor acerca de los impactos que los modelos RC tienen sobre las experiencias de trabajo y la práctica profesional de esos profesionales. Résumé: La croissance de la formation professionnelle pour les professionnels de la santé des nourrissons et de la petite enfance a nécessité la mise en place d'approches innovatrices et durables afin de remplir les besoins de formation et de consultation de supervision réflective (RSC) de la santé mentale du nourrisson et de la petite enfance (IECMH). Une étude pilote de 12 mois d'un modèle de groupe de consultation réflective (abrégé RC en anglaise) dans un état des Etats‐Unis a inclus des consultants IECMH, des spécialistes des subventions, des superviseurs et des gestionnaires de programme (n = 38) et leurs consultants de groupe de réflexion (n = 6). Cette évaluation pilote a présenté l'opportunité de concevoir une étude évaluant les impacts de la RC sur les professionnels de la santé des nourrissons et de la petite enfance. Cette méthode d'étude mixte a inclus une évaluation des compétences en pratique réflective des personnes consultées et de leurs expériences de leur travail. Les résultats ont inclus une pratique d'auto‐efficacité réflective plus élevée (auto‐rapportée par les consultés) et une utilisation de compétences de pratique de réflexion plus élevée. Bien qu'il n'y ait pas eu de changements dans la réalisation personnelle, l'épuisement émotionnel ou les résultats de dépersonnalisation de l'Inventaire de Burnout de Maslach (MBI) les résultats qualitatifs ont indiqué une baisse du burnout et une augmentation de la pratique basée sur la relation au travers des rôles professionnels. Cette étude pilote unique offre un exemple d'une approche organisationnelle de l'institution de la RC avec un grand éventail de professionnels de la santé des nourrissons et de la petite enfance et offre des renseignements très utiles sur les impacts des modèles de RC sur l'expérience du travail de tels professionnels et leur pratique professionnelle. Zusammenfassung: Die Implementierung eines mehrstufigen, reflektierten Beratungsmodells in ein landesweites System zur beruflichen Weiterbildung in der Säuglings‐ und Kleinkinderbetreuung: Auswertung eines Pilotprojekts Das Wachstum in der beruflichen Entwicklung von Fachkräften im Bereich der frühkindlichen Betreuung hat die Einführung neuer, nachhaltiger Ansätze erforderlich gemacht, um den Bedarf an Ausbildung und reflektierter Supervision im Bereich der psychischen Gesundheit von Kleinkindern (IECMH) zu decken. Das 12‐monatige Pilotprojekt eines landesweiten Gruppenmodells für reflektierte Beratung (RC) in den USA umfasste IECMH‐Berater:innen, Förderungsspezialist:innen, Supervisor:innen, Programmmanager:innen (n = 38) und ihre Gruppenberater:innen (n = 6). Die Pilotevaluierung bot die Gelegenheit, eine Studie zu konzipieren, die die Auswirkungen von RC auf Fachkräfte im Bereich der frühkindlichen Betreuung untersuchte. Die mixed‐methods Studie umfasste eine Beurteilung der Fähigkeiten der Berater:innen innerhalb der reflektierten Praxis und ihrer Arbeitserfahrung. Zu den Ergebnissen gehörte, dass die Befragten nach eigenen Angaben ihre Selbstwirksamkeit in der reflektierten Praxis erhöht haben und ihre Fähigkeiten zur reflektierten Praxis verstärkt einsetzen. Während sich die Ergebnisse des Maslach Burnout Inventory (MBI) in Bezug auf persönliche Leistung, emotionale Erschöpfung oder Depersonalisierung nicht veränderten, deuteten die qualitativen Ergebnisse auf einen Rückgang des Burnouts und eine Zunahme der beziehungsbasierten Praxis in allen beruflichen Rollen hin. Dieses einzigartige Pilotprojekt ist ein Beispiel für einen organisatorischen Ansatz zur Einführung von RC bei einem breiten Spektrum von Fachkräften im Bereich der frühkindlichen Betreuung und liefert wertvolle Informationen über die Auswirkungen von RC‐Modellen auf die Arbeitserfahrung und die berufliche Praxis dieser Fachkräfte. 抄録: 全州乳幼児保育教育専門家育成システムへの複層的省察コンサルテーションモデ ルの導入における、パイロット版の評価 乳幼児期を対象とした人材の専門性発達における成長は、乳幼児精神保健 (IECMH) トレーニングと省察的スーパービジョン・コンサルテーション (RSC) のニーズを満たすために、斬新で持続可能なアプローチの導入を必要としている。米国の全州を対象とした省察的コンサルテーション (RC) グループモデルの12カ月間の試験的実施には、IECMHコンサルタント・助成金専門家・スーパーバイザー、プログラムマネージャー (n = 38) と, そのグループの省察的コンサルタント (n = 6) が含まれていた。この試験的な評価を機に、RCが乳幼児期の専門家に与える影響を評価する研究を計画した。混合法研究で、相談者の省察的実践のスキルと臨床経験の評価を行った。その結果、相談者の自己申告によると、省察的実践の自己効力感が高まり、省察的実践スキルの使用が増えた。また、マスラック・バーンアウト・インベントリー (MBI) の個人的達成感、感情的疲労感、脱人格化の結果には変化が見られなかったものの、定性的な調査結果では、燃え尽き症候群が減少し、専門家としての役割を超えた関係性に基づく実践が増加したことが示された。このユニークな試みは、幅広い乳幼児期の専門家にRCを導入するための組織的なアプローチの一例であり、RCモデルがそのような専門家の臨床経験や専門的な実践に与える影響についての貴重な情報をもたらしている。 摘要: 婴幼儿劳动力职业发展的增长需要实施新颖、可持续的方法, 以满足婴幼儿心理健康 (IECMH) 培训和反思性监督咨询 (RSC) 的需求。为期12个月的美国全州反思性咨询 (RC) 小组模型试点包括了IECMH顾问、拨款专家、主管和项目负责人 (n = 38) 以及小组反思顾问 (n = 6)。这项试点评估提供了一个机会来设计一项研究, 用以评估RC对婴幼儿专业人员的影响。混合方法研究包括了评估咨询师的反思实践技能和工作经验。调查结果包括了咨询师自我报告的反思性实践自我效能感的提高以及反思性实践技能使用的增加。虽然Maslach职业倦怠量表 (MBI) 的个人成就感、情绪耗竭或去人格化结果没有变化, 但定性研究结果表明, 职业角色的职业倦怠降低, 基于关系的实践增加。这一独特的试点提供了一个组织方法的例子, 用于与广泛的婴幼儿专业人员建立RC, 并产生关于RC模式对这些专业人员的工作经验和专业实践的影响的宝贵信息。 ملخص: تنفيذ نموذج استشاري تأملي متعدد المستويات في نظام تطوير مهني لتعليم الرضع والأطفال في مرحلة الطفولة المبكرة على مستوى الولاية: تقييم نموذج تجريبي مع تزايد الاهتمام بالتطوير المهني للقوى العاملة في مرحلة الطفولة المبكرة والرضع استلزم الأمر تنفيذ مناهج جديدة ومستدامة لتلبية احتياجات تدريب الرضع في مجال الصحة النفسية للطفولة المبكرة (IECMH) والاستشارات المتعلقة بالإشراف التأملي (RSC) . اشتمل النموذج التجريبي لمجموعة الاستشارات التأملية (RC) على مستشاري الصحة النفسية للرضع والأطفال (IECMH ) واختصاصيي المنح والمشرفين ومديري البرامج (العدد = 38) ومستشاريهم (العدد = 6). قدم التقييم التجريبي فرصة لتصميم دراسة قيمت تأثير الاستشارات التأملية على المتخصصين في الطفولة المبكرة والرضع. تضمنت الدراسة ذات الأساليب المختلطة تقييمًا لمهارات الممارسة التأملية للمستشارين وخبراتهم في عملهم. تضمنت النتائج زيادة الكفاءة الذاتية للممارسة التأملية التي أبلغ عنها الاستشاريون بأنفسهم وزيادة استخدام مهارات الممارسة التأملية. بينما لم تكن هناك تغييرات في الإنجاز الشخصي على مقياس ماسلاش للإنهاك (MBI) ، أو الإرهاق العاطفي ، أو نتائج تبدد الشخصية ، أشارت النتائج النوعية إلى انخفاض في الإرهاق وزيادة في الممارسة القائمة على العلاقات عبر الأدوار المهنية. يقدم هذا النموذج التجريبي الفريد مثالاً على النهج التنظيمي لتأسيس الاستشارات التأملية مع مجموعة واسعة من المتخصصين في الطفولة المبكرة والرضع ويقدم معلومات قيمة حول تأثيرات نماذج الاستشارة التأمليه على خبرة العمل والممارسة المهنية لهؤلاء المهنيين.